PROPERTIES OF GAMMA-AMINO ACID AND ITS IMPORTANCE IN MEDICINE. - Khaydarova HA; Niyazov LN (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This article examines the importance of gamma-aminobutyric acid and amino acids for the human body. Their functions are also described. All the functions of GABA in the body are covered in detail.